High-throughput bioengineering of homogenous and functional human-induced pluripotent stem cells-derived liver organoids via micropatterning technique - Xu, Xiaodong; Jiang, Shanqing; Gu, Longjun; Li, Bin; Xu, Fang; Li, Changyong; Chen, Pu (Frontiers in Bioengineering and Biotechnology, 2022)
Human pluripotent stem cell-derived liver organoids are emerging as more human-relevant in vitro models for studying liver diseases and hepatotoxicity than traditional hepatocyte cultures and animal models. The generation of liver organoids is based on the Matrigel dome method. However, the organoids constructed by this method display significant heterogeneity in their morphology, size, and maturity. Additionally, the formed organoid is randomly encapsulated in the Matrigel dome, which is not convenient for in situ staining and imaging. Here, we demonstrate an approach to generate a novel type of liver organoids via micropatterning technique. This approach enables the reproducible and high-throughput formation of bioengineered fetal liver organoids with uniform morphology and deterministic size and location in a multiwell plate. The liver organoids constructed by this technique closely recapitulate some critical features of human liver development at the fetal stage, including fetal liver-specific gene and protein expression, glycogen storage, lipid accumulation, and protein secretion. Additionally, the organoids allow whole-mount in-situ staining and imaging. Overall, this new type of liver organoids is compatible with the pharmaceutical industry's widely-used preclinical drug discovery tools and will facilitate liver drug screening and hepatotoxic assessment.